Life after ruxolitinib: Reasons for discontinuation, impact of disease phase, and outcomes in 218 patients with myelofibrosis. Issue 6 (20th December 2019) - Palandri, Francesca; Breccia, Massimo; Bonifacio, Massimiliano; Polverelli, Nicola; Elli, Elena M.; Benevolo, Giulia; Tiribelli, Mario; Abruzzese, Elisabetta; Iurlo, Alessandra; Heidel, Florian H.; Bergamaschi, Micaela; Tieghi, Alessia; et al.
Abstract : Background: After discontinuing ruxolitinib, the outcome of patients with myelofibrosis reportedly has been poor. The authors investigated whether disease characteristics before the receipt of ruxolitinib may predict drug discontinuation in patients with myelofibrosis and whether reasons for drug discontinuation, disease phase at discontinuation, and salvage therapies may influence the outcome. Methods: A centralized electronic clinical database was created in 20 European hematology centers, including clinical and laboratory data for 524 patients who received ruxolitinib for myelofibrosis. Results: At 3 years, 40.8% of patients had stopped ruxolitinib. Baseline predictors of drug discontinuation were: intermediate‐2–risk/high‐risk category (Dynamic International Prognostic Score System), a platelet count <100 ×10 9 per liter, transfusion dependency, and unfavorable karyotype. At last contact, 268 patients (51.1%) had discontinued therapy, and the median drug exposure was 17.5 months. Fifty patients (18.7%) died while taking ruxolitinib. The reasons for discontinuation in the remaining 218 patients were the lack (22.9%) or loss (11.9%) of a spleen response, ruxolitinib‐related adverse events (27.5%), progression to blast phase (23.4%), ruxolitinib‐unrelated adverse events (9.2%), and allogeneic transplantation during response (5.1%). The median survival after ruxolitinib was 13.2 months and was significantly better in the 167 patients who discontinued ruxolitinib in chronic phase (27.5 vs 3.9 months for those who discontinued in blast phase; P < .001). No survival differences were observed among patients who discontinued ruxolitinib in chronic phase because of lack of response, loss of response, or ruxolitinib‐related adverse events. The use of investigational agents and/or ruxolitinib rechallenge were associated with improved outcome. Conclusions: The survival of patients with myelofibrosis after discontinuation of ruxolitinib is poor, particularly for those who discontinue in blast phase. Salvage therapies can improve outcome, emphasizing the need for novel therapies. Abstract : In real‐world data from 524 patients who received ruxolitinib for myelofibrosis, the incidence of and risk factors associated with drug discontinuation were investigated along with how reasons for discontinuation, disease phase at discontinuation, and salvage therapies may influence outcomes. At 3 years, higher risk category, lower platelet count, unfavorable karyotype, and transfusion dependency at the start of ruxolitinib were associated with a greater probability of drug discontinuation; and outcomes were significantly better in patients who discontinued in chronic phase versus blast phase and in those who received investigational agents and/or ruxolitinib rechallenge.